A New In Situ Prepared MOF‐Natural Polymer Composite Electrolyte for Solid Lithium Metal Batteries with Superior High‐ Rate Capability and Long‐Term Cycling Stability at Ultrahigh Current Density. Issue 3 (15th November 2022) - Guan, Jiazhu; Feng, Xinping; zeng, Qinghui; Li, Zhenfeng; Liu, Yu; Chen, Anqi; Wang, Honghao; Cui, Wei; Liu, Wei; Zhang, Liaoyun
Abstract: Lithium metal batteries hold promise for energy storage applications but suffer from uncontrolled lithium dendrites. In this study, a new composite membrane based on modified natural polymer and ZIF‐67 is designed and prepared by the in situ composite method for the first time. Among them, a modified natural polymer composed of lithium alginate (LA) and polyacrylamide (PAM) can be obtained by electrospinning. Importantly, the polar functional groups of natural polymers can interact by hydrogen bonding and MOFs can construct lithium‐ion transport channels. Consequently, compared with LA‐PAM electrolyte without MOF, the electrochemical stability window of ZIF‐67‐LA‐PAM electrolyte becomes wider from 4.5 to 5.2 V, and the lithium‐ion transference number ( t Li+ ) enhances from 0.326 to 0.627 at 30°C. It is worth noting that the symmetric cells with ZIF‐67‐LA‐PAM have superior stable cycling performance at 40 and 100 mA cm −2, and a high rate at 10C and 20C for LFP cells. Besides, the cell with NCM811 high‐voltage cathode can run stably for 400 cycles with an initial discharge capacity of 136.1 mAh g −1 at 0.5C. This work provides an effective method for designing and preparing MOF‐natural polymer composite electrolytes and exhibits an excellent application prospect in high‐energy‐density lithium metal batteries. Abstract : A natural polymer composite electrolyte is prepared by in situ synthesis of ZIF‐67 on a modified lithium alginate electrospinning membrane. The assembled cells can run stably for 1300 h at 100 mA cm −2 for symmetric cells, 1600 cycles at 20C for LFP cells, and even 400 cycles at 2C for pouch cells. The obtained electrolyte can also well adapt to the NCM811 electrode.